Pengembangan Distribusi Air Bersih di Kecamatan Polombangkeng Utara Kabupaten Takalar - Arsyad (PSTS FT UIM, 2024)
Water is an essential element of the environment and a source of life for humans. Both humans and life on Earth cannot exist without water. Water will become more and more necessary as development, education, and living standards rise (Mampuk et al., 2014). The purpose of this study is to assess the drinking water network's capacity in Takalar Regency's North Polombangkeng District and to examine the viability of expanding drinking water distribution. The Hardy cross method, the geometric method, and the arithmetic method are all used in this study. The Takalar Regency's inhabitants are able to get their drinking water needs met thanks to the presence of shallow wells that are about 8 meters deep and have a 10 liters per second capacity. These wells are pumped to the top of a 250 m3 reservoir. This facility provides services to 13 public hydrant units and 386 house connections. The installation is hampered by the extremely low water flow during the dry season, which necessitates the assistance of a water tanker from PDAM Takalar city. Based on the analysis's findings, the North Polombangkeng District's clean water network can currently handle 10 liters per second. The Takalar City PDAM IPA, with a capacity of 645 liters/second, can provide clean water for the potential development of distribution in the North Polombangkeng District, although only 80 liters/second are actually used. As for the next ten years, the development of clean water distribution in Takalar Regency's North Polombangkeng District is still quite safe, with a projected 38,859 liters/second (3,357,417.6 liters/day) need for clean water in 2023.